Association of coarctation of aorta with Turner syndrome: a case report - Khan, Musawer; Imtiaz, Sana; Shoaib, Muhammad; Tariq, Malaika; Zahra, Sadia; Sardar, Awais; Khan, Asif Ullah; Kamil, Kamil Ahmad (Frontiers in Pediatrics, 2025)
BackgroundMonosomy 45,X is commonly associated with congenital heart defects, particularly coarctation of the aorta (CoA). In this case, the patient developed respiratory distress due to hemodynamic instability from a large bidirectional patent ductus arteriosus (PDA) shunt and systemic hypoperfusion secondary to CoA, which complicated diagnosis and management.Case presentationWe report a 34-week premature female neonate weighing 1.94 kg, delivered via lower segment cesarean section (LSCS) due to oligohydramnios and intrauterine growth restriction. She exhibited characteristic features of Turner syndrome, including a webbed neck, low-set ears, widely spaced nipples, and lymphedema of the hands and feet. Karyotyping confirmed a 45,X monosomy. Echocardiography revealed a bicuspid aortic valve, juxtaductal coarctation of the aorta, a moderate-sized PDA with a bidirectional shunt, and suspected pulmonary hypertension. A contrast-enhanced CT aortogram confirmed the coarctation. The patient was managed with mechanical ventilation, continuous positive airway pressure (CPAP), surfactant therapy, and phototherapy. Rescue transcatheter balloon angioplasty was performed for the coarctation, followed by PDA ligation and surgical coarctation repair at a tertiary center, resulting in marked clinical improvement.